SPATIAL AGGLOMERATION AND ECONOMIC DEVELOPMENT WITH THE INCLUSION OF INTERREGIONAL TOURISM - Zhang, Wei-Bin (Economic Annals, 2017)
The purpose of this paper is to extend Uzawa’s two-sector model of a national economy to an economy with any number of regions and interregional tourism. The paper studies interregional economic development with interactions between wealth accumulation, economic structure, interregional trade and tourism under assumptions of profit maximization, utility maximization, and perfect competition. The model is unique in interregional neoclassical growth theory in that it introduces endogenous tourism within a general equilibrium framework. The model is built on microeconomic foundations. It not only extends the well-known Solow growth model and the Uzawa two-sector model to a national economy with any number of heterogeneous regional economies, but also introduces tourist flows between regions. We demonstrate that the movement of the J-regional economy can be described by J+1 differential equations. We simulate the movement of a national economy with three regions. We show that the dynamic system has a unique equilibrium. We carry out comparative dynamic analysis with regard to the propensity to tour a region, the cost of travel from one region to another, the total factor productivity of a region’s industrial sector, the total factor productivity of a region’s service sector, the propensity to save, the parameters of a region’s amenity, the propensity to consume housing, and the national population. We demonstrate the dynamic effects of these changes on national GDP, wealth, and tourist patterns.